Placed in a Global Overview of Literature on Honey Identification. Book Review: El-Labban, M. Beekeeper’s Guide for Pollen Identification of Honey, 2nd ed.; Northern Bee Books: Hebden Bridge, UK, 2023; ISBN: 978-9953-0-5184-0 - Henry Hooghiemstra (Quaternary, 2025)
Melissopalynology, the study of honey, is a flourishing area within palynological research [...]